1997
DOI: 10.1016/s0885-3924(96)00267-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a continuing education program on nurses' pain assessment practices

Abstract: Surgical nurses from five Dutch general hospitals participated in a continuing education program on pain assessment and management. A pretest-posttest controlled intervention study revealed that the program led to an increase in the quality of activities relevant to taking pain histories. Although this increase in quality was most apparent 1 month after the program, it was still observable 6 months after the program. There were, however, no effects on the number of activities relevant to taking pain histories,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 14 publications
0
40
0
1
Order By: Relevance
“…To date, many studies from Western countries have identified knowledge and skill deficits about palliative care in medical professionals, [1][2][3][4][5][6][7][8] and multiple interventions have been tried to improve these deficits. [9][10][11][12][13][14] However, to date, there have been no similar studies in Japan. In addition, existing studies have predominantly focused on pain control, and broader areas of palliative care have rarely been systemically investigated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, many studies from Western countries have identified knowledge and skill deficits about palliative care in medical professionals, [1][2][3][4][5][6][7][8] and multiple interventions have been tried to improve these deficits. [9][10][11][12][13][14] However, to date, there have been no similar studies in Japan. In addition, existing studies have predominantly focused on pain control, and broader areas of palliative care have rarely been systemically investigated.…”
Section: Methodsmentioning
confidence: 99%
“…Sources included the Palliative Care Quiz for Nursing, 1,2 literature review, in-depth interviews with 5 nurses, and discussions among ourselves. [3][4][5][6][7][8][9][10][11][12][13][14][16][17][18][19][20][21][22][23][24][25][26] Most questions were based on the published evidence from empirical studies. [3][4][5][6][7][8][9][10][11][12][13][14][16][17][18][19][20][21][22][23][24][25][26] The face validity and acceptability of the questionnaire was confirmed by a pilot test.…”
Section: Questionnaire and Outcome Measuresmentioning
confidence: 99%
“…Pain education for nursing students and continuing education for practising nurses is deemed necessary to enhance pain management. Structured pain education programmes for nursing students (Watt-Watson et al, 2004) and practising nurses (Francke et al, 1997) have led to improved pain management practices.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is not completely clear which changes in nurses' interventions are related to the decrease in patients' pain intensity. Other parts of the study revealed that the quality of nurses' psychosocial, physical and relaxation interventions, and the quality of nurses' analgesic administrations improved (Francke, 1996;Francke et al, 1996b and1997). It is not very likely that effects on pain intensity are caused by quality improvements of psychosocial interventions, since there are no significant 12.1 (7.1) 9.6 (6.6) breast day 2 exp.…”
Section: Discussionmentioning
confidence: 98%
“…Within this scope, a CE programme on pain assessment and management was evaluated in both nurses and patients. In Francke (1996) and Francke et al (1996b and1997) the effects of the CE pro-gramme on nurses were described. To summarize, the programme led to an increase in the quality of nurses' pain assessment practices.…”
Section: Introductionmentioning
confidence: 99%